What Counts as a Developmental Sequence? Exemplar‐Based L2 Learning of English Questions. Issue 1 (March 2015) - Eskildsen, Søren W.; Hulstijn, Jan H.; Ellis, Rod; Eskildsen, Søren W.
<x xml:space="preserve">Abstract</x> Drawing on usage‐based linguistics and its exemplar‐based path of language learning, from recurring multiword expressions to increasingly abstract, schematized constructions, this article examines evidence for the exemplar‐based developmental sequences for yes/no interrogatives and WH interrogatives in English as a second language (L2). The empirical point of departure is an audio‐visual corpus of American English L2 classroom interaction. The longitudinal data come from two Spanish‐speaking students from Mexico and show that they learned yes/no interrogatives and WH interrogatives pattern by pattern. The degree of schematization was found to differ between them. In both cases, however, their resources for asking questions were not found to emerge at once on the basis of acquired syntactic rules (e.g., inversion) to be deployed across diverse linguistic patterns in a broad‐sweeping manner, but emerged as lexically specific, exemplar‐based patterns at different points in time.